Pengaruh Disiplin Kerja, Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Di Kantor Kecamatan Mataru Kabupaten Alor - Handayani Karmaley (Peneliti.net, 2023)
The purpose of this study was to determine the effect of work discipline, work motivation and work environment on employee performance in the Mataru District Office, Alor Regency. This type of research is a quantitative description. Samples were taken using saturated sample technique. The sample in this study were 30 employees. Data collection tools used are observation, interviews, and literature studies. The data analysis model used to answer the hypothesis is multiple analysis, t test, F test. This research instrument test is used to measure the level of validity, reliability and classic assumptions from the answers to the research questionnaire. Based on the results of the validity test for each variable with a Pearson correlation value ≥ 0.3, the results of the validity test for each variable are declared valid. The reliability test results for each variable with a Crobatc Alpha value ≥ 0.6, the reliability test results for each variable are declared reliable. Kolmogrov-Smirnov Normality test results with sig. ≥ 0.05 then the test results are declared normal. The results of the heteroscedasticity test showed that the value of each independent variable was > 0.05, so there was no heteroscedasticity in this study. The results of the multicollinearity test show that the VIF value > tolerance means that multicollinearity does not occur in this study. The results of the linearity test between the dependent variable and the independent variable show that the deviation from linearity value is > 0.05, so there is a relationship between the dependent variable and the independent variable. The analytical method used is multiple linear regression analysis technique. The results with the t test to answer the first, second, and third hypotheses, while multiple linear regression analysis simultaneously used the F test to determine the fourth hypothesis, namely to determine the effect of work discipline, work motivation and work environment on employee performance in the Mataru District Office, Alor Regency . Based on the results of the calculation of multiple linear regression analysis partially and simultaneously obtained a significance value of the Work Discipline variable of 0.000, the Work Motivation variable of 0.009, the Work Environment variable of 0.000, and the simultaneous effect of the value of the significance test F is 0.000b, the results of the test t and the F test is smaller than alpha (0.05), then the hypothesis testing proposed in this study is as follows: there is an influence of work discipline, work motivation and work environment on employee performance in the Mataru District Office, Alor Regency.